Socialização de gênero na educação infantil: uma análise a partir da perspectiva das crianças - Sandro Vinicius Sales dos Santos (2016)
This thesis seeks to understand five-year old children´s perspective about gender relations. From a multidisciplinary theoretical framework constituted at the intersection among gender, social studies of childhood, sociology, anthropology, pedagogy of childhood and early childhood education this research analyzed the sense/meaning produced by children about gender relations that they experienced in a public early childhood school. More specifically, the research intends to identify and to analyze gender symbologies that are present in children´s daily lives; to describe how these symbologies are perceived and expressed by boys and girls; to analyze how the children experience gender relations in the social interactions among them and among adults. It is a qualitative research, an ethnography, developed with five-years old children in a public early childhood institution that took place in the city of Belo Horizonte, Minas Gerais. This study used the following data production tools: participant observation (using photographic records and field notes); interviews (with children and adults); and drawings articulated with oral conversations. The study had the participation of eighteen boys and seven girls and their teachers (the reference teacher woman and the support teacher man). The data produced in the field provided an understanding of different strategies of gender socialization that occur in the early childhood school. The investigation, also, allowed the identification of different gender socializations processes that intersect inside this institution (in some situations they articulate themselves and in others they contradict themselves). By approaching children´s perspectives, we could realize that boys and girls produce meanings about gender relations in the multiples socials processes that are complex and sometimes, contradictories. In addition, they interact simultaneously with culture (in its material and symbolic aspects), with adults and their peers. This complexity stimulates children to produce meanings about gender relations by means of combination of different action logic: sometimes seeking to conform to the rules about what is to meant to be a boy or girl, sometimes seeking a better comprehension about the existent differences about male and female, and sometimes experiencing new ways to be in the world in order to construct masculine and feminine identities.